2003
DOI: 10.1038/nature01497
|View full text |Cite
|
Sign up to set email alerts
|

Glycine binding primes NMDA receptor internalization

Abstract: NMDA (N-methyl-d-aspartate) receptors (NMDARs) are a principal subtype of excitatory ligand-gated ion channel with prominent roles in physiological and disease processes in the central nervous system. Recognition that glycine potentiates NMDAR-mediated currents as well as being a requisite co-agonist of the NMDAR subtype of 'glutamate' receptor profoundly changed our understanding of chemical synaptic communication in the central nervous system. The binding of both glycine and glutamate is necessary to cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
347
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(378 citation statements)
references
References 26 publications
13
347
1
3
Order By: Relevance
“…This result suggested that the increases of glycine in the interstitium by theanine might have influenced dopamine release via glycine receptors. Although glycine is known as a major inhibitory neurotransmitter, glycine combines with the glycine binding site of the NMDA receptor and enhances excitatory neurotransmission (Xu et al 1999;Kuhse et al 1995;Nong et al 2003). Glycine enhanced NMDA evoked dopamine release, and 7-chloro-kynurenate, an NMDA antagonist, acting on a glycine site, markedly reduced this response (Martinez et al 1992); however, 5,7-DCKA injection did not prevent the increase of dopamine concentration by theanine injection in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…This result suggested that the increases of glycine in the interstitium by theanine might have influenced dopamine release via glycine receptors. Although glycine is known as a major inhibitory neurotransmitter, glycine combines with the glycine binding site of the NMDA receptor and enhances excitatory neurotransmission (Xu et al 1999;Kuhse et al 1995;Nong et al 2003). Glycine enhanced NMDA evoked dopamine release, and 7-chloro-kynurenate, an NMDA antagonist, acting on a glycine site, markedly reduced this response (Martinez et al 1992); however, 5,7-DCKA injection did not prevent the increase of dopamine concentration by theanine injection in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…Although this seems to be the case in mature neurons, NMDARs move rapidly into and out of synapses in developing neurons 15,18,34 . It is likely that synaptic removal of NMDARs involves a combination of lateral diffusion 15,34 and endocytosis [16][17][18] . Although the mechanisms have been unclear, this process is almost certainly determined by a balance between interactions with scaffolding proteins that anchor receptors at the PSD, and interactions with adaptors that target NMDARs to the endocytic machinery for membrane removal 25 .…”
Section: Nmdar Mobility and Receptor Endocytosismentioning
confidence: 99%
“…Substantial evidence also supports a role for exocytic and endocytic receptor cycling in controlling AMPAtype glutamate receptor abundance at synapses during synaptic plasticity, but NMDARs have conventionally been thought to be stably fixed within the postsynaptic density (PSD). Challenging this view, recent studies have revealed that NMDARs can move rapidly in and out of the neuronal surface [14][15][16][17][18][19][20] . Atleast some forms of NMDAR exocytic and endocytic trafficking require synaptic activity 21 or ligand binding 17,22 ,23 , and may initiate synaptic changes that lead to synapse stabilization or elimination during development 16,23 . Despite recent progress, our knowledge of how postsynaptic NMDARs are linked to and regulated by the endocytic machinery is only just emerging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent reports demonstrate that the dominant endogenous co-agonist for NMDAR neurotoxicity is D-serine but not glycine (Shleper et al, 2005). Furthermore, high concentrations of glycine prime NMDAR internalization (Nong et al, 2003), which may lead to a concentration-dependent dual regulation of NMDAR-mediated responses. Additional studies report that GlyRs can affect GABAergic responses through crossinhibition between GlyRs and GABA A receptors (GABA A Rs) (Li and Xu, 2002;Li et al, 2003).…”
Section: Introductionmentioning
confidence: 99%